2022
DOI: 10.1038/s41598-022-20662-1
|View full text |Cite
|
Sign up to set email alerts
|

Silicon modifies C:N:P stoichiometry and improves the physiological efficiency and dry matter mass production of sorghum grown under nutritional sufficiency

Abstract: Silicon (Si) may be involved in the modification of C:N:P stoichiometry and in physiological processes, increasing sorghum growth and grain production. The objective was to evaluate the effect of Si supply on C:N:P:Si stoichiometry, physiological response, growth, and grain production of sorghum. The experiment was carried out in pots with four concentrations of Si: 0; 1.2; 2.4; and 3.6 mmol L−1 in a completely randomized design, with six replicates. Physiological attributes and dark green color index were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…The induction of a new homeostatic balance of C:N:P caused by Si under water deficit conditions also occurs in 30-day pre-sprouted seedlings [ 13 ], and 90-days [ 32 ], 150-days [ 33 ] and 160-days [ 31 ] sugarcane plants. The induction of a new C:N:P homeostasis is not only restricted in sugarcane plants, but has also been observed in forage [ 26 , 27 ], quinoa [ 35 ], wheat [ 36 ], sorghum and sunflower [ 17 , 37 ]. This helps to consolidate another benefit of Si in the cultivation of sugarcane that also occurs in sugarcane ratoons, but it is not restricted only to this crop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of a new homeostatic balance of C:N:P caused by Si under water deficit conditions also occurs in 30-day pre-sprouted seedlings [ 13 ], and 90-days [ 32 ], 150-days [ 33 ] and 160-days [ 31 ] sugarcane plants. The induction of a new C:N:P homeostasis is not only restricted in sugarcane plants, but has also been observed in forage [ 26 , 27 ], quinoa [ 35 ], wheat [ 36 ], sorghum and sunflower [ 17 , 37 ]. This helps to consolidate another benefit of Si in the cultivation of sugarcane that also occurs in sugarcane ratoons, but it is not restricted only to this crop.…”
Section: Discussionmentioning
confidence: 99%
“…A known and sustainable alternative to attenuate stress in crops is the beneficial element Si. It may also affect plants without stress [ 15 17 ]. An advantage of this element is its relatively low cost compared to nutrients present in conventional fertilizers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…such as Saccharum officinarum L. [ 19 , 39 , 41 – 44 ], Chenopodium quinoa Willd. [ 34 ], Sorghum bicolor (L.) Moench [ 17 , 33 ], and Triticum aestivum L. [ 35 ]. However, this is the first study to detect the role of Si in changing the stoichiometric ratio C:N:P in bean plants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the role of Si in replacing C in organic compounds that make up the cell wall of plants, especially lignin and cellulose [ 32 ]. Recent research indicates that Si uptake can lead to a new homeostatic balance of C:N:P, as observed in different species such as Sorghum bicolor (L.) Moenchand, Helianthus annuus L. [ 17 , 33 ], Chenopodium quinoa Willd. [ 34 ], Triticum aestivum L. [ 35 ], Panicum maximum L. [ 36 ], Phragmites australis [ 37 ], Medicago sativa [ 38 ], and Saccharum officinarum L. [ 19 , 39 – 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Si application has the potential to alter N assimilation rates in some Si-accumulating plants, such as rice and wheat [8,21,22]. This also means that plant uptake and utilization of different forms of inorganic N could be affected by altered available Si pools following bamboo expansion.…”
Section: Introductionmentioning
confidence: 99%